2017
DOI: 10.1111/jcmm.13443
|View full text |Cite
|
Sign up to set email alerts
|

ALDH2 gene G487A polymorphism and coronary artery disease: a meta‐analysis including 5644 participants

Abstract: Several studies indicate the mitochondrial Aldehyde Dehydrogenase‐2 (ALDH2) gene G487A polymorphism may be correlated with coronary artery disease (CAD) susceptibility, but a clear consensus has yet to be reached. To elucidate the relationship between the ALDH2 gene G487A polymorphism and CAD within the Chinese population, a meta‐analysis of 5644 subjects from nine individual studies was performed. Pooled odds ratios (ORs) and their corresponding 95% confidence intervals were assessed using random or fixed‐eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…These lend some support to our hypothesis concerning greater susceptibility to CVD-related conditions associated with ALDH2*2. Broadly, these findings are consistent with Asian studies that found increased risks associated with ALDH2*2 for CVD (Jo et al, 2007;Li et al, 2018), diabetes (Li et al, 2017;Yin et al, 2016), hypertension (Jia et al, 2015), and low-density lipoprotein cholesterol (Kotani et al, 2012). Though most of these studies did not consider drinking, interactions between alcohol consumption and ALDH genotypes have also been reported in a small number of studies.…”
Section: Discussionsupporting
confidence: 83%
“…These lend some support to our hypothesis concerning greater susceptibility to CVD-related conditions associated with ALDH2*2. Broadly, these findings are consistent with Asian studies that found increased risks associated with ALDH2*2 for CVD (Jo et al, 2007;Li et al, 2018), diabetes (Li et al, 2017;Yin et al, 2016), hypertension (Jia et al, 2015), and low-density lipoprotein cholesterol (Kotani et al, 2012). Though most of these studies did not consider drinking, interactions between alcohol consumption and ALDH genotypes have also been reported in a small number of studies.…”
Section: Discussionsupporting
confidence: 83%
“…The mutant genotypes and allele frequencies of rs671 are markedly different among different populations and are particularly more prevalent in East Asian populations (Chinese, Japanese and Korean individuals) than in other populations (38, 39). Many studies have demonstrated that the ALDH2 rs671 G>A polymorphism maybe associated with the development of various diseases, such as digestive system cancer (40), diabetes (41), coronary heart disease (42), and ischemic stroke (43), especially in East Asians.…”
Section: Discussionmentioning
confidence: 99%
“…The ALDH2*2 (rs671) variant is an independent risk factor of coronary heart disease in many population-based studies [164168]. In 248 patients with coronary heart disease, the variant ALDH2 genotypes (GG & GA) were associated with increased serum levels of 4-HNE, severity of coronary artery stenosis and atherosclerosis [169].…”
Section: Therapies Targeting Mitochondria In Heart Failurementioning
confidence: 99%